Avaliação da intenção de uso de um sistema de e-learning por alunos de uma instituição de ensino superior do Rio de Janeiro - Abreu, Michele Amaral dos Santos Silva (2012)
The increasing advancement of Information and Communication Technologies (ICTs) has been offering its users a wide range of potential uses. In the educational context, for example, they are gaining a wide representation, particularly in programs of Distance Education (DE) (Maia, 2003), especially within the higher education institutions, which make use of tools such as e -learning to process effectiveness of distance education. This study aims to evaluate variables that influence students in a classroom course, adopt a positive intention to accept a system of e-learning as a tool for learning in the educational environment of an Institution of Higher Education. From the literature review was identified that the Technology Acceptance Model - TAM by Davis (1989) would be more robust to the proposed evaluation. A questionnaire was applied, which resulted in a sample of 584 students. Data were analyzed using Structural Equation Modeling - SEM. The results confirmed the validity of most of the hypotheses except only for the effect of perceived ease of use on attitude toward use. The other links provided in the original TAM model were also confirmed in this study, as well as the influence of previous experience on the Internet on the perceived ease of use and quality of information on perceived usefulness.